IMF Lending and Banking Crises - Papi, Luca (IMF Working Papers; Working Paper ;, 2015)
This paper looks at the effects of International Monetary Fund (IMF) lending programs on banking crises in a large sample of developing countries, over the period 1970-2010. The endogeneity of the IMF intervention is addressed by adopting an instrumental variable strategy and a propensity score matching estimator. Controlling for the standard determinants of banking crises, our results indicate that countries participating in IMF-supported lending programs are significantly less likely to experience a future banking crisis than nonborrowing countries. We also provide evidence suggesting that compliance with conditionality and loan size matter.